2008
DOI: 10.1080/02640410701468863
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with physical activity referral uptake and participation

Abstract: Factors associated with physical activity referral uptake and participation. Journal of Sports Sciences, 26 (2). pp. 217-224. ISSN 0264-0414Official URL: http://www.ncbi.nlm.nih.gov/pubmed/17943595 DOI: http://dx.doi.org/10.1080/02640410701468863 EPrint URI: http://eprints.glos.ac.uk/id/eprint/374 DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 29 publications
5
95
0
3
Order By: Relevance
“…The research design adopted is noteworthy in that it contrasts with other studies in the exercise referral literature in 2 specific ways. Firstly, the majority of studies published in this area adopt a quantitative approach [28][29][30][31][32][33], although some studies do adopt a qualitative approach [34][35][36][37]. Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' experiences of involvement with an exercise referral scheme and its impact on sustaining physical activity levels for 3 months after completion of the programme.…”
Section: Methods Designmentioning
confidence: 99%
“…The research design adopted is noteworthy in that it contrasts with other studies in the exercise referral literature in 2 specific ways. Firstly, the majority of studies published in this area adopt a quantitative approach [28][29][30][31][32][33], although some studies do adopt a qualitative approach [34][35][36][37]. Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' experiences of involvement with an exercise referral scheme and its impact on sustaining physical activity levels for 3 months after completion of the programme.…”
Section: Methods Designmentioning
confidence: 99%
“…Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' changing perceptions over a 6-month time period for the following QoL indicators of (i) self-efficacy, (ii) selfmanagement, (iii) chronic fatigue and (iv) increasing energy levels [12,16,18]. Secondly, the deployment of 3 data collection and analysis phases contrasts markedly with traditional data collection schedules in the literature, which tend to adhere to the life-cycle of the exercise referral scheme, that is, pre and post a 12-week intervention [15,26,[30][31][32][33]. Some studies do include a 12-week followup [34,35].…”
Section: Methods Designmentioning
confidence: 99%
“…Such approaches 25 may lead to increased numbers of men being referred into exercise referral schemes. This is particularly important when considering the positive influence that GPs can have on motivating patients to attend such schemes (James et al 2008;Horne et al, 2010), and that twice as many men complete exercise referral schemes than women (Gidlow et al, 2007;James et al, 2008;Lee et al, 2009). In turn, further training for health professionals should consider techniques to reduce 'direct' approaches during consultation which are founded on perceptions of male-specific behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies have shown that the number of men participating in ERS can be disproportionately lower than that of women (see Dugdill et al 2005 [1098 men, 1685 women], Gidlow et al 2007Gidlow et al [1386Gidlow et al men, 2182 women], James et al 2009 [455 men, 860 women]). Despite these differences, prior research has also identified 5 that women are less likely to complete schemes than men (Gidlow et al 2007, James et al 2008, Morton et al 2008. Explanations for low completion rates amongst women include greater domestic and social responsibility (Mackey et al 2002;Aitchison 2003).…”
mentioning
confidence: 99%